Modelling the predictors and outcomes of brand experience: evidence from the chained fast food brand / Rozita Naina Mohamed - Naina Mohamed, Rozita (Institute of Graduate Studies, UiTM, 2014)
In today’s overcrowded and highly competitive marketplace, ‘Brand Experience’ (BE) can be the most privileged tool for differentiation. Customer’s feeling, emotion and interactions will contribute to the overall perception of the brand experience. Undoubtedly, it is critical to gain insights into the key drivers of ‘brand experience’ and subsequently ascertain its outcomes in order to design effective marketing strategies for market growth and perhaps business sustainability. The principal aim was to develop an integrative novelty model of brand experience and examine the predictors and outcomes of brand experiences of the four most prominent fast food brand share in Malaysia namely, Mc Donald’s, Kentucky Fried Chicken, Marrybrown and A & W. The study applies SOR Model (Mehrabian-Russell, 1974), and other related branding models to a sample of 450 adult respondents who reside in chosen urban areas in Malaysia.